Local residents and tourists’ opinion on the effects of boating activity towards Kilim waterways - Ibrahim, Putri Haryati; Mohd Ismail, Widad; Mansor, Mazlina (Universiti Putra Malaysia Press, 2019)
Heritage sites within Kilim Karst Geoforest Park consist of geology, archaeology, ecology, history and culture. Therefore, both tourism and resource conservation should be integrated in order to benefit human and natural resources. This paper presents research that identifies the opinion of tourists and local residents on the effects of boating activities towards natural resource conservation in Kilim Karst Geoforest Park, Langkawi. 320 structured questionnaires were distributed to tourists, local residents in Kilim and staffs who are in charged in the tourism operation of Kilim Karst Geoforest Park including staff of Langkawi Development Authority (LADA), Koperasi Kampung Kilim Langkawi Berhad (KKKLB) and Komuniti Pengurusan Sumber Perikanan (KPSP). The study managed to gather 93% with response rate (n=299) that consist tourists (65), local residents of Kilim (145) and staff (89). Based on the analyses conducted, it was found that boating activities contributed to the pollutions along Kilim waterways in many ways for instance, oil spills and waste disposals. Majority of the respondents agreed that high boats speed increased strong waves, which lead to depletion of mangrove trees and affecting aquatic life. Kilim has become one of the preferred destinations for nature lovers since the area has been given the Geopark and has received countless of tourist arrivals. Nevertheless, this situation had also affected natural resources of the area. Thus, people who involved in tourism activities and the management of Kilim Karst Geoforest Park should concern and possessed adequate knowledge on natural resource conservation so that the area can be experienced by the future generations.